Interventions employed to improve intrahospital handover: a systematic review. Issue 7 (8th May 2014) - Robertson, Eleanor R; Morgan, Lauren; Bird, Sarah; Catchpole, Ken; McCulloch, Peter
Abstract : Background: Modern medical care requires numerous patient handovers/handoffs. Handover error is recognised as a potential hazard in patient care, and the information error rate has been estimated at 13%. While accurate, reliable handover is essential to high quality care, uncertainty exists as to how intrahospital handover can be improved. This systematic review aims to evaluate the effectiveness of interventions aimed at improving the quality and/or safety of the intrahospital handover process. Methods: We searched for articles on handover improvement interventions in EMBASE, MEDLINE, HMIC and CINAHL between January 2002 and July 2012. We considered studies of: staff knowledge and skills, staff behavioural change, process change or patient outcomes. Results: 631 potentially relevant papers were identified from which 29 papers were selected for inclusion (two randomised controlled trials and 27 uncontrolled studies). Most studies addressed shift-change handover and used a median of three outcome measures, but there was no outcome measure common to all. Poor study design and inconsistent reporting methods made it difficult to reach definite conclusions. Information transfer was improved in most relevant studies, while clinical outcome improvement was reported in only two of 10 studies. No difference was noted in the likelihood of success across four types of intervention. Conclusions: The current literature does not confirm that any methodology reliably improves the outcomes of clinical handover, although information transfer may be increased. Better study designs and consistency of the terminology used to describe handover and its improvement are urgently required.